2020
DOI: 10.1002/agj2.20043
|View full text |Cite
|
Sign up to set email alerts
|

Modelling root water uptake under deficit irrigation and rewetting in Northwest China

Abstract: The spatial and temporal distribution of root water uptake (RWU) under deficit irrigation are critical factors for crop growth. The SWAP (soil–water–atmosphere–plant) model was applied to analyze the pattern of RWU for winter wheat (Triticum aestivum L.) under three irrigation levels: no water deficit (100% evapotranspiration [ET]), moderate water deficit (80% ET) and severe water deficit (60% ET). The 2–yr experiments indicated that SWAP was highly accurate (mean relative error [MRE] <21.7%, root mean square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(129 reference statements)
1
4
0
Order By: Relevance
“…Three irrigation levels were impleme g each stage: 100% (no water deficit), 80% (moderate deficit) and 60% (severe deficit) of a easured by the large weighing lysimeter with sufficient irrigation treatment (CK, namely 1) (Figure 3). The range of the device was 0 to 6 t, and the measurement accuracy was less [35]. The size of the lysimeter is consistent with the plot.…”
Section: Experimental Designsupporting
confidence: 66%
See 3 more Smart Citations
“…Three irrigation levels were impleme g each stage: 100% (no water deficit), 80% (moderate deficit) and 60% (severe deficit) of a easured by the large weighing lysimeter with sufficient irrigation treatment (CK, namely 1) (Figure 3). The range of the device was 0 to 6 t, and the measurement accuracy was less [35]. The size of the lysimeter is consistent with the plot.…”
Section: Experimental Designsupporting
confidence: 66%
“…This was because T a was closely related to root water uptake. Different irrigation amounts caused variations in soil water status, and these effects were reflected in the changes in root morphology (root length and density distribution) and physiological functions (root vitality and water uptake) [35,[65][66][67]. Under water stress, roots were vulnerable to drought and died.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clement et al [22] concluded that deep-rooted crops have the advantage of obtaining deep soil water under drought conditions by comparing the water absorption status of the roots of different types of perennial crops. Wang et al [23] defined the water content corresponding to the 95% RWU of the control treatment as the critical water content and concluded that the critical water content was different in different growth stages of winter wheat. In addition, the absolute RWU of different types of soil was affected by ET 0 [24].…”
Section: Introductionmentioning
confidence: 99%